Assessment of Dietary Intake Patterns and Their Correlates among University Students in Lebanon - Salameh, Pascale; Jomaa, Lamis; Issa, Carine; Farhat, Ghada; Salamé, Joseph; Zeidan, Nina; Baldi, Isabelle, for the Lebanese National Conference for Health in University Research Group (Frontiers in Public Health, 2014)
Introduction : Unhealthy dietary habits are a major risk factor for chronic diseases, particularly if adopted during early adulthood. In a study conducted on a large sample of university students from both public and private universities in Lebanon, we observed differences in obesity prevalence between males and females. Given this difference, the objective of this analysis was to define the different dietary patterns among university students, focusing on correlation with gender and body mass index (BMI). Methods : A cross-sectional study was carried out on 3384 students, using a proportionate cluster sample of Lebanese students from both public and private universities. Results : Three dietary patterns were identified among university youth namely, vegetarian/low calorie diet (mainly plant food while avoiding ‘western’ food, composite dishes, and bread); mixed diet (high consumption of plant food, followed by composite dishes, bread, and a low consumption of western type food), and finally the westernized diet (high consumption of white bread and western food, and a strong avoidance of plant food and composite dishes). We observed significant differences between males and females in terms of their reported food intake and dietary patterns. Females were particularly more prone to adopt the vegetarian/low calorie diet than males (ORa=1.69; p<0.001), while males were more likely to adopt a westernized diet (ORa=1.51; p<0.001), seemingly in private universities (p=0.053). Students with high income and obese students (BMI ≥ 30 kg/m2) were more likely to consume vegetarian/low calorie diets (P<0.05). Conclusion: Male university students, despite having a higher BMI, reported a higher consumption of food according to a westernized dietary pattern as compared to female university students in Lebanon, while the latter reported a higher adoption of a vegetarian diet. Health promotion programs are needed among university youth in Lebanon to address their dietary intakes.